A Hazelnut-Enriched Diet Modulates Oxidative Stress and Inflammation Gene Expression without Weight Gain. (4th July 2019) - Di Renzo, Laura; Cioccoloni, Giorgia; Bernardini, Sergio; Abenavoli, Ludovico; Aiello, Vincenzo; Marchetti, Marco; Cammarano, Andrea; Alipourfard, Iraj; Ceravolo, Ida; Gratteri, Santo
Abstract : Introduction . Inflammation is associated with obesity condition and plays a pivotal role in the onset and progression of many chronic diseases. Among several nutraceutical foods, hazelnuts (Corylus avellana L.) are considered an excellent anti-inflammatory and hypolipidemic food being the second richest source of monounsaturated fatty acids among nuts and because they are rich in vitamins, minerals, and phenolic compounds. Materials and Methods . A prospective pilot clinical trial on 24 healthy volunteers who consumed daily, as a snack, 40 g of hazelnuts (261.99 kcal/1096.17 kJ) for six weeks was conducted. Anthropometric measurements, body composition analysis, and nutrigenomic analysis on 12 anti-inflammatory and antioxidant genes were evaluated at baseline (T0) and after hazelnut intervention (T1). Results . No significant changes were detected on body composition analysis after hazelnut consumption. Conversely, significant upregulation was detected for SOD1 (2 − Δ Δ Ct = 2.42 ), CAT (2 − Δ Δ Ct = 2.41 ), MIF (2 − Δ Δ Ct = 4.12 ), PPAR γ (2 − Δ Δ Ct = 5.89 ), VDR (2 − Δ Δ Ct = 3.61 ), MTHFR (2 − Δ Δ Ct = 2.40 ), and ACE (2 − Δ Δ Ct = 2.16 ) at the end of the study. Conclusions . According to emerging evidences, hazelnut consumption does not lead to weight gain probably due to the improvement of the body's antioxidant capacity by the upregulation of genes implied in oxidant reactions and inflammation.